Randomized Trial of Compression Duration After Transradial Cardiac Catheterization and Intervention. Issue 2 (3rd February 2017) - Lavi, Shahar; Cheema, Asim; Yadegari, Andrew; Israeli, Zeev; Levi, Yaniv; Wall, Sabrina; Alemayehu, Mistre; Parviz, Yasir; Murariu, Bogdan‐Dorian; McPherson, Terry; Syed, Jaffer; Bagur, Rodrigo
Abstract : Background: Radial artery occlusion is a known complication following transradial cardiac catheterization. A shorter duration of postprocedural radial clamp time may reduce radial artery occlusion (RAO) but might be associated with incomplete hemostasis. Methods and Results: In total, 568 patients undergoing transradial diagnostic cardiac catheterization were randomly assigned to either 20 minutes (ultrashort) or 60 minutes (short) hemostatic compression time using patent hemostasis. Subsequently, clamp pressure was reduced gradually over 20 minutes. Access site hemostasis and RAO were assessed after clamp removal. Repeated assessment of RAO was determined at 1 week in 210 (37%) patients. Mean age was 64±11 years, and 30% were female. Percutaneous coronary intervention was performed in 161 patients. RAO immediately after clamp removal was documented in 14 (4.9%) and 8 (2.8%) patients in the 20‐ and 60‐minute clamp application groups, respectively ( P =0.19). The incidence of grade 1 hematoma was higher in the 20‐minute group (6.7% versus 2.5%, P =0.015). RAO at 1 week after the procedure was 2.9% and 0.9% in the 20‐ and 60‐minute groups, respectively ( P =0.36). Requirement for clamp retightening (36% versus 16%, P =0.01) was higher among patients who had RAO. Need for clamp retightening was the only independent predictor of RAO ( P =0.04). Conclusions: Ultrashort radial clamp application of 20 minutes is not preferable to a short duration of 60 minutes. The 60‐minute clamp duration is safe and provides good access site hemostasis with low RAO rates. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02269722.